Extracorporeal shock wave therapy versus dexamethasone iontophoresis as a treatment for symptomatic knee osteoarthritis - Abu El Kasem, Shimaa Taha; Ahmed Abdalbary, Sahar; Mabrouk, Mohamed I.; Moustafaa, Engy Badreldin S.; Abonour, Asmaa; Mohamed, Rania R. (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Purpose. The goal of this pilot study was to compare and evaluate the efficacy of extracorporeal shock wave therapy (ESWT) and dexamethasone sodium phosphate (DEX-P) iontophoresis in patients who have unilateral symptomatic knee OA (KOA).Methods. Pre-post single-blind randomised experimental trial. The therapeutic program was performed twice per week for 4 weeks. Sixty patients with unilateral symptomatic KOA were randomly divided into three groups. Intensity of pain, pressure threshold for pain, knee function, and knee range of motion (ROM) were measured before and after therapy in all three groups.Results. The improvement in the shock wave group was significantly greater than the iontophoresis group.Conclusions. ESWT has a superior therapeutic effect in patients with symptomatic KOA.
Keywords: knee osteoarthritis; extracorporeal shock wave therapy; dexamethasone sodium phosphate iontophoresis